Key Elements Affecting the Library’s CFU Concentration in Taiwan - Bang-Lee Chang; Han-Kuang Tien; Yong-Jun Lin; Gary Li-Kai Hsiao (Complexity)
Public libraries are popular gathering places, so understanding the factors that contribute to colony-forming unit (CFU) concentrations and how to minimize them is essential. This study aimed to investigate the factors that affect CFU concentrations in a public library, using air sampling (Bioluminescent ATP-assay) and statistical analysis software (SPSS) to collect and analyze data. The findings indicated that the CFU concentration in the library was significantly influenced by the air quality surrounding the building, the number of library visitors, and the hygiene and health of both visitors and employees. Additionally, indoor temperature and humidity were found to be key factors affecting CFU concentration. These findings suggest the need for better ventilation and air filtration systems, as well as regular cleaning and disinfection in public libraries. Furthermore, research is recommended to investigate other potential factors that may impact indoor air quality in public spaces.